Comunicação, consumo e envelhecimento: (in)comunicação com o consumidor mais velho - Mine, Tania Zahar (2016)
The objective of this thesis is to analyse the employed brand strategies that aim to convene older people as consumers, how do they target their communication to older people, and what type of senior citizen they are promoting in their campaigns. The present research project has as foundation the joint of three academic areas: communications, consumption practices and ageing studies. With accelerated population ageing a new target is constituted, product and services companies adapt their communication strategies to contemplate gray market opportunities. The focus are the advertising campaign of six brands, aired on internet, that form the corpus of the study. The internet selection is justified by its relevancy as an advertising medium, for allowing the content dissemination targeted to specific consumer segments and for its use has been exponentially growing among seniors. The corpus analysis is based on a netnographic observation of brand content for its sites and digital social networks. The used methodology was content analysis followed by critical description analysis. According to the achieved results, it could be concluded that the advertising campaign stimulate the valued and desired senior role model construction. The portrayed lifestyle congregates various values and themes, that constitute a young senior portrait, enthusiastic, independent and that plans, as a competent manager, the different aspects of his life, in other words, that he does not see himself as old. This well succeed portrait has become a must to be followed and constitutes the only way to ageing